Experimental investigation on the deflagration load under unconfined methane-air explosions. (1st December 2016) - Bao, Qi; Fang, Qin; Yang, Shigang; Zhang, Yadong; Xiang, Hengbo; Chen, Li; Li, Zhan
Highlights: Varied concentration (7.5–11.5%) and volume (1–27 m 3 ) of gas were considered. Effects of volume, concentration and distance on deflagration load were analyzed. A set of prediction models for deflagration load were proposed. Abstract: 9 batches of unconfined methane-air deflagration tests were conducted to investigate the influential factors on the deflagration load. The methane-air mixture was filled in the cubic tents with different volumes of 1 m 3, 8 m 3 and 27 m 3 . Methane concentrations varied from 7.5% to 11.5%, covering both lean and rich combustion regimes. The ground overpressure was recorded by using the piezoresistive sensors. An ideal film was validated before the tests. The effects of the methane concentration and gas volume on the deflagration load were analyzed. Based on the results, a new prediction model for the unconfined methane-air deflagration load was proposed. In addition, the model was compared with some existing models.